2018
DOI: 10.1007/s10029-018-1814-0
|View full text |Cite
|
Sign up to set email alerts
|

Preventative laparoscopic repair of Petersen’s space following gastric bypass surgery reduces the incidence of Petersen’s hernia: a comparative study

Abstract: 667 patients were taken to LGBP, and of which 5 presented internal hernias. From the 346 patients who had Petersen´s herniorrhaphy performed, one developed signs of an internal hernia at 22 months follow-up and was subsequently confirmed later with laparoscopy (0.02%). Of the 321 patients not having had Petersen's space closure, 4 developed Petersen's internal hernia at an average of 22-month post-op, incidence of 0.1%. We analyzed and compared our results with those reported in the literature. Petersen's spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…All these patients required bowel resection with either anastomosis or stoma formation. The duration between the onset of the symptoms and presenting to the hospital was the important contributing factor, not only for the higher rates of advanced ischemia of bowel wall, but also influence the outcome in these patients, similar findings have been observed by other authors in their studies [23][24][25] . In the current study majority of the patients belongs to the villages, due to lack of adequate medical facilities, and by ignorance about the seriousness of the condition they were trying with local physicians and quacks to get relief from the symptoms, this appears to be the reason for their late presentation.…”
Section: Discussionsupporting
confidence: 87%
“…All these patients required bowel resection with either anastomosis or stoma formation. The duration between the onset of the symptoms and presenting to the hospital was the important contributing factor, not only for the higher rates of advanced ischemia of bowel wall, but also influence the outcome in these patients, similar findings have been observed by other authors in their studies [23][24][25] . In the current study majority of the patients belongs to the villages, due to lack of adequate medical facilities, and by ignorance about the seriousness of the condition they were trying with local physicians and quacks to get relief from the symptoms, this appears to be the reason for their late presentation.…”
Section: Discussionsupporting
confidence: 87%
“…In recent years, a series of studies has demonstrated that closure of Petersen space or mesenteric defect could significantly reduce the risk of internal hernia ( 13 , 15 , 16 ). Therefore, it has been recommended as a routine step during gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…La prevención de la hernia interna con el cierre profiláctico de los defectos mesentéricos durante la cirugía primaria no es un método estandarizado actualmente [2] . No se ha demostrado evidencia de que el cierre del espacio de Petersen evite la aparición de una hernia interna, pero parece disminuir su incidencia [3,4,5] , por lo que actualmente se recomienda su cierre con una sutura continua no reabsorbible durante la cirugía primaria [6,7] .…”
unclassified